2008
DOI: 10.1111/j.1540-4609.2007.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficiency and Effectiveness of Grading Through the Use of Computer‐Assisted Grading Rubrics

Abstract: This study tests the use of computer-assisted grading rubrics compared to other grading methods with respect to the efficiency and effectiveness of different grading processes for subjective assignments. The test was performed on a large Introduction to Business course. The students in this course were randomly assigned to four treatment groups based on the grading method. Efficiency was measured by the professor's time to grade the assignments; effectiveness was measured by a student satisfaction survey. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 11 publications
3
20
0
2
Order By: Relevance
“…Gardner, Sheridan, and Andreas (2012) argue that 'time is the most challenging factor when marking' and divides time into an allocation for 'administrative tasks (marking per se) and time spent on engaging with student's work and providing individual feedback' (p. 392). Several other researchers (Ahoniemi and Karavirta 2009;Anglin et al 2008;Milne, Heinrich, and Morrison 2008) confirm that e-tools provide more time to provide individual feedback reduces paper usage and generally improve the manual grading process. Tutors in this study indicated several positive reasons for using computerassisted rubrics as shown in the following responses: Overall the strength of this tool lies in the fact that once the online rubric was completed by the tutor, the results and the feedback were immediately available for the students to access.…”
Section: Benefitsmentioning
confidence: 99%
“…Gardner, Sheridan, and Andreas (2012) argue that 'time is the most challenging factor when marking' and divides time into an allocation for 'administrative tasks (marking per se) and time spent on engaging with student's work and providing individual feedback' (p. 392). Several other researchers (Ahoniemi and Karavirta 2009;Anglin et al 2008;Milne, Heinrich, and Morrison 2008) confirm that e-tools provide more time to provide individual feedback reduces paper usage and generally improve the manual grading process. Tutors in this study indicated several positive reasons for using computerassisted rubrics as shown in the following responses: Overall the strength of this tool lies in the fact that once the online rubric was completed by the tutor, the results and the feedback were immediately available for the students to access.…”
Section: Benefitsmentioning
confidence: 99%
“…When the student does so, they are presented with a pop-up screen that displays the criteria used for evaluating the assignment. Atkinson and Lim (2013) and Anglin et al (2008) reported that the interactive rubric was instrumental in reducing grading time. Goomas (in press) reported that using the realtime interactive rubric resulted in less rework and fewer omissions of the required criteria of a writing assignment.…”
mentioning
confidence: 97%
“…Several studies have reported on the effectiveness and efficiency in performing these assessments by automating and embedding an interactive rubric in an LMS (Anglin, Anglin, Schumann, & Kaliski, 2008;Atkinson & Lim, 2013;Goomas, in press). The way the interactive rubric works is that the student is instructed to click on the Rubric icon.…”
mentioning
confidence: 98%
“…Computer-assisted grading rubrics are essential to improve the efficiency and effectiveness of grading [Anglin et al, 2008] and [Auvinen et al, 2009]. Although some commercially available CAA tools provide automatically contextualized feedback [Santos et al, 2009] and [Cebrián-Robles et al, 2014], and some Learning Management Systems (LMS) [Atkinson and Lim, 2013] provide rubric functionality, currently available implementation only support static rubrics that does not provide any flexibility to adapt to different learning scenarios.…”
Section: Supplementary Backgroundmentioning
confidence: 99%
“…Computer-assisted grading methods are essential to improve the efficiency and effectiveness of assessment through rubrics [Anglin et al, 2008] and [Auvinen et al, 2009]. The use of static rubrics are not appropriate in CAD, as common problems do not lend themselves to only "right" or "wrong" answers [Reid and Cooney, 2008].…”
Section: Introductionmentioning
confidence: 99%